Quality of life and mental health status of glaucoma patients - Kopilaš, Vanja; Kopilaš, Mirko (Frontiers in Medicine, 2024)
Glaucoma, a leading cause of irreversible blindness worldwide, poses significant challenges to patients' quality of life (QOL) and mental well-being. This study aimed to investigate the complex interplay between clinical, demographic, and psychological factors and their impact on QOL among patients diagnosed with glaucoma. A cohort of 201 glaucoma patients, with a mean age of 70 years, participated in the study. Descriptive analyses revealed that participants reported living with a glaucoma diagnosis for an average of 13.38 years, highlighting the chronic nature of the disease in the cohort. Comorbidity was shown to be in close relationship with QOL, where with additional health problems have lower QOL scores (M=34.86, SD=18.25), as well as higher levels of anxiety (M=10.64, SD=5.38) and depression (M=13.42, SD=7.37). Correlation analyses further unveiled robust associations between clinical characteristics and psychological outcomes, with lower visual acuity strongly correlated with reduced QOL (rR=-0.74, pR<0.001; rL=-0.78, pL<0.001) and higher levels of anxiety and depression. Additionally, longer duration of glaucoma diagnosis was moderately associated with poorer QOL (r=0.56, p<0.001) and increased psychological distress, highlighting the cumulative burden of living with the disease over time. Mediation analyses indicated that duration of diagnosis partially mediated the relationship between depression and QOL, as well as anxiety and QOL, suggesting that the prolonged experience of living with glaucoma may exacerbate the impact of psychological distress on QOL. These findings underscore the importance of holistic patient care approaches that address both the physical and psychological aspects of glaucoma to improve patient outcomes and enhance overall well-being.